Pembuatan Bahan Ajar Digital Untuk SMK Kartini Batam - Serly Serly; Milenia Panca Wijaya2 (ConCEPt - Conference on Community Engagement Project, 2021)
The design of digital teaching materials is carried out to solve the problems faced by SMK Kartini Batam regarding the teaching materials needed during distance learning since the COVID-19 pandemic. This change in the learning system causes many students to experience difficulties in the process of understanding the material. So that to simplify the learning process for both teachers and students, the authors of the preparation of digital teaching materials which contain accounting computerized material. The methods used in the implementation of community service activities (PkM) are interviews and observations. The author designed teaching materials with outputs in the form of powerpoints and videos to facilitate the online learning process at SMK Kartini Batam. The author recommends providing teaching materials in the form of modules, powerpoints, and instructional videos for other subjects in PkM further efforts to facilitate students' understanding and also the completeness of the material.